PTSD Symptoms Mediate the Relationship Between Sexual Abuse and Substance Use Risk in Juvenile Justice–Involved Youth. (August 2018) - Sanders, Jasmyn; Hershberger, Alexandra R.; Kolp, Haley M.; Um, Miji; Aalsma, Matthew; Cyders, Melissa A.
Juvenile justice–involved youth face disproportionate rates of sexual abuse, which increases the risk of post-traumatic stress disorder (PTSD) and substance use disorders (SUDs), both of which are associated with poor long-term outcomes. The present study tested two mediation and moderation models, controlling for age, race, and history of physical abuse, with gender as a moderator, to determine whether PTSD symptoms serve as a risk factor and/or mechanism in the relationship between sexual abuse and substance use. Data were examined for 197 juvenile justice–involved youth (mean age = 15.45, 68.9% non-White, 78.4% male) that completed court-ordered psychological assessments. Results indicated that PTSD symptoms significantly mediated the relationship between sexual abuse and drug (β = 3.44, confidence interval [CI] [0.26, 7.41]; test for indirect effect z = 2.41, p = .02) and alcohol use (β = 1.42, CI [0.20, 3.46]; test for indirect effect z = 2.23, p = .03). PTSD symptoms and gender were not significant moderators. Overall, PTSD symptoms mediate the relationship between sexual abuse and SUDs in juvenile justice–involved youth, which suggests viability of targeting PTSD symptoms as a modifiable risk factor to reduce the effects of sexual abuse on substance use in this high-risk population.